Bertelot et Kulikowski au Luxembourg. Conservation d’un exceptionnel ensemble de moulages - Emily Rawlinson-Mazeri (In Situ)
The recent acquisition by the Musée des Monuments français/Cité de l’architecture et du patrimoine of twelve plaster casts of statues at the Luxembourg palace by Guillaume Bertelot (1580-1648), offers an opportunity to analyse the role played by casts in an important restoration operation on a building towards the end of the 19th century and to highlight the debates created by this initiative. The contribution also raises the question of the status of these plaster casts, which represent unique archeological testimonies of seventeenth-century works now lost.